Exploration of potential objective and subjective daily indicators of sleep health in normal sleepers - Allen, SF; Elder, GJ; Longstaff, LF; Gotts, ZM; Sharman, R; Akram, U; Ellis, JG (Dove Medical Press, 2018)
Purpose: While the concept of “sleep health” has only recently been defined, how it relates to both subjective and objective sleep parameters is yet to be determined. The current study aimed to identify potential indicators of poorer sleep health, from subjective and objective daily sleep characteristics, in normal sleepers.